Poguntano Herba Extract Immunostimulant Activities (Picriafel-terraeLour). in Immunosupression Rats Infected by Staphylococcus aureus Against Total Leukocytes and Differential Leukocytes - Ningtias, Anggitha; Rosidah; Yuandani (Talenta Publisher, 2021)
Poguntano (Picriafel-terraeLour.) is a medicinal plant in North Sumatra that has been used in traditional medicine to treat degenerative diseases.Poguntano extract contains flavonoid compounds that have the potential to be developed into immunomodulators. This study showed the immunostimulant activity of poguntano herb n-hexane extract (PHNHE), poguntano herb ethyl acetate extract (PHEAE) and poguntano herb ethanol extract (PHEE) in immunosuppressed rats infected with Staphylococcus aureus. The evidence of poguntano herb as an immunomodulator was carried out by testing total leukocytes and differential leukocytes. Poguntano herb n-hexane extract (PHNHE) can not increase the total and differential leukocytes; Poguntano herb ethyl acetate extract (PHEAE) and poguntano herb ethanol extract (PHEE) can increase the total and differential leukocytes in immunosuppressed rats induced by Staphylococcus aureus.